Erectile dysfunction in cirrhosis is impacted by liver dysfunction, portal hypertension, diabetes and arterial hypertension - Paternostro, Rafael (Liver Int, 2018)
BACKGROUND: Although several risk factors for erectile dysfunction may be present in patients with cirrhosis, data on the actual prevalence and cause of erectile dysfunction is limited. The International Index of Erectile Function‐5 (IIEF‐5) is a well‐validated survey to determine the presence and severity of erectile dysfunction in men. We assessed (i) the prevalence and severity of erectile dysfunction, and (ii) risk factors for erectile dysfunction in patients with cirrhosis. METHODS: In this prospective study, erectile dysfunction was defined as: absent (>21 IIEF‐5‐points), mild (12‐21) and severe (5‐11). Patients with overt hepatic encephalopathy, active alcohol abuse, extrahepatic malignancy, previous urologic surgery, previous liver transplantation and severe cardiac conditions were excluded. RESULTS: Among n = 151 screened patients, n = 41 met exclusion criteria and n = 30 were sexually inactive. Thus, a final number of n = 80 male patients with cirrhosis were included. Patient characteristics: age: 53 ± 9 years; model for end‐stage liver disease score (MELD): 12.7 ± 3.9; Child‐Pugh score (CPS) A: 30 (37.5%), B: 35 (43.8%), C: 15 (18.7%); alcohol: 38 (47.5%), viral: 25 (31.3%), alcohol/viral: 7 (8.8%) and others: 10 (12.5%). The presence of erectile dysfunction was found in 51 (63.8%) patients with 44 (55%) and 7 (8.8%) suffering from mild‐to‐moderate and moderate‐to‐severe erectile dysfunction. Mean MELD and hepatic venous pressure gradient (HVPG) were significantly higher in patients with erectile dysfunction (P = .021; P = .028). Child‐Pugh score C, MELD, creatinine, age, arterial hypertension, diabetes, low libido, low testosterone and high HVPG were associated with the presence of erectile dysfunction. Interestingly, beta‐blocker therapy was not associated with an increased risk. In multivariate models, arterial hypertension (OR: 6.36 [1.16‐34.85]; P = .033), diabetes (OR: 7.40 [1.31‐41.75]; P = .023), MELD (OR: 1.19 [1.03‐1.36]; P = .015) and increasing HVPG (n = 48; OR: 1.11 [1.002‐1.23]; P = .045) were independent risk factors for the presence of erectile dysfunction. CONCLUSION: About two‐thirds of male patients with cirrhosis show erectile dysfunction. Severity of liver dysfunction, portal hypertension, arterial hypertension and diabetes were identified as risk factors for erectile dysfunction.